ANALISA DAN PENGEMBANGAN SISTEM INFORMASI JUMLAH MASYARAKAT PENGANGGUR DINAS TENAGA KERJA DAN TRANSMIGRASI - Fabianus Yayan; Taufan Rifai; Hidayatullah Himawan (Jurusan Teknik Informatika, 2012)
Advances in science and technology is growing. Almos every agency of government has felt the impact of technology advances. In order to meet the performance and mobility of the employees would not want to participate and take advantage of the technologycal sophistication. Advances in technology, innovation and efficiency continue to be done to support the performance of employees in a varity ways, including viewing and analyzing th enumber of people unemployed in a region. So this study is more on providing information and analysis on the spred factor of unemployment in a region.